Penyuluhan Webinar Kajian Fatwa MUI Tentang Akad Murabahah di Komunitas Pegiat Ekonomi Syariah di Surakarta - Alam, Azhar; Cahyaningrum, Linda Islam; Rama, Nabila Rahmawati; Hamidah, Raisa Aribatul (LPPM UMRI, 2022)
The community of Islamic economic activists in Surakarta and surrounding areas is committed to advancing the sharia economy. They form a community to carry out discussions and outreach studies to increase Islamic economic literacy. Financial literacy in general or mainly in Islamic economics is still very low in Indonesian society, so it requires significant efforts to increase literacy through outreach activities. Murabahah contract is the most common contract widely used in Islamic economic activities by Islamic financial institutions, banking, and microfinance. This outreach activity aims to increase the knowledge of the community of Islamic economic activists in Surakarta and its surroundings regarding the study of the fatwa on murabahah contracts and current issues related to one of the muamalah contracts. Contract problems and disputes that occur in the relationship of Islamic financial institutions with customers or customers are also dominated by Murabahah contracts. Murabahah contract is also a contract with a nominal amount of transactions large enough to take the form of a sharia financing syndicate with a Murabahah contract. This counseling activity suggests that every party involved in a murabahah contract is obliged and needs to uphold what has been contracted.